Eight-handed Vishnu - 047 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Right hand side of the statue is damaged. On the left hand side, top most hand is holding a bow, which is usually how Lord Rama is depicted. The hand below the bow is holding one of the usual artefacts of Vishnu, the conch shell. The bottom right hand is holding the Japamala - the prayer beads.